2019
DOI: 10.3390/atmos10110666
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerosol-Cloud Cycling on Aqueous Secondary Organic Aerosol Formation

Abstract: Chemical processing of organic material in aqueous atmospheric aerosols and cloudwater is known to form secondary organic aerosols (SOA), although the extent to which each of these processes contributes to total aerosol mass is unclear. In this study, we use GAMMA 5.0, a photochemical box model with coupled gas and aqueous-phase chemistry, to consider the impact of aqueous organic reactions in both aqueous aerosols and clouds on isoprene epoxydiol (IEPOX) SOA over a range of pH for both aqueous phases, includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 56 publications
(80 reference statements)
2
27
0
Order By: Relevance
“…This indicates that nitrogen, as a nucleophile, is more important than the acid-catalyzed aldol condensation, which is consistent with the observation of Kampf et al (2012Kampf et al ( , 2016 and Yi et al (2018). A theoretical analysis of glyoxal condensation in the presence of ammonia conducted by Tuguldurova et al (2019) describes different imidazole formation pathways by the formation of key intermediates, namely ethanediimine, diaminoethanediol, and aminoethanetriol, required for the imidazole ring cyclization. These authors reported that the imine concentrations are very low due to the high-energy barriers for imine formation.…”
Section: Surface Filmssupporting
confidence: 80%
“…This indicates that nitrogen, as a nucleophile, is more important than the acid-catalyzed aldol condensation, which is consistent with the observation of Kampf et al (2012Kampf et al ( , 2016 and Yi et al (2018). A theoretical analysis of glyoxal condensation in the presence of ammonia conducted by Tuguldurova et al (2019) describes different imidazole formation pathways by the formation of key intermediates, namely ethanediimine, diaminoethanediol, and aminoethanetriol, required for the imidazole ring cyclization. These authors reported that the imine concentrations are very low due to the high-energy barriers for imine formation.…”
Section: Surface Filmssupporting
confidence: 80%
“…SOA formed from uptake of isoprene epoxydiols (IEPOX SOA) (Paulot et al, 2009) appears to be the major confirmed aqueous SOA product globally, being important in all highisoprene and lower-NO regions (Hu et al, 2015), along with glyoxal formed from isoprene and aromatics (Fu et al, 2008). Formation of SOA in clouds was investigated in the southeast US and found to be not statistically significant (Wagner et al, 2015). These pathways have been implemented into three-dimensional global atmospheric chemistry and climate models using two different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…organic aerosols (Zhang et al, 2018). Other pathways may contribute to SOA to some extent and may add to the predicted SOA formed by partitioning, including biogenic SOA from auto-474 oxidation (Bianchi et al, 2019;Pye et al, 2019a), in-cloud SOA formation that may be less 475 dependent on acidity than aqueous SOA (Tsui et al, 2019), a small but underestimated contribution of anthropogenic SOA (Schroder et al, 2018;Shah et al, 2019), and other possible 477 mechanisms (Schwantes et al, 2019). Further quantifying the relative importance of the different 478 pathways will allow a more accurate quantification of the anthropogenic influence on biogenic 479 SOA and the associated radiative forcing.…”
Section: Summary and Discussionmentioning
confidence: 99%